Expression Analysis of ABC Transporters Reveals Differential Functions of Tandemly Duplicated Genes in Caenorhabditis elegans - Zhao, Z.; Sheps, J.A.; Ling, V.; Fang, L.L.; Baillie, D.L.
We have previously identified 60 predicted ABC transporter genes in the Caenorhabditis elegans genome and classified them into eight groups. As an initial step towards understanding how these putative ABC genes work in worms, we generated promoter-fluorescent protein fusions for the entire family to address when and where these genes are turned on in vivo. Both Aequoria green fluorescent protein (GFP)and Discosoma red fluorescent protein (RFP)were used as reporters in our transgenic assay. Observable expression is more frequently seen from fusions to genes in subfamilies B, C, D and E than those in subfamilies A and G. Sixteen worm ABC genes are found in tandem duplications, forming two four-gene clusters and four two-gene clusters. Fifteen out of the 16 duplicated gene promoters drove different or partially overlapping expression patterns, suggesting active functions for these duplicated genes. Furthermore, our results suggest that an internal promoter can cause differential expression of genes within an operon. Finally, our observations suggest that it is possible for coding sequences to function as a regulatory region for a neighbouring gene.
Keywords: ABC TRANSPORTER; CAENORHABDITIS ELEGANS; PROMOTER; GREEN FLUOR-ESCENCE PROTEIN (GFP); EXPRESSION